A Young Woman with Common Variable Immunodeficiency: The Role of Thorough Medical History and Physical Examination in Accurate Diagnosis - Amirhossein Khodadadi; Rozita Khodashahi (Case Reports in Medicine)
Common variable immunodeficiency (CVID) is a rare immunodeficiency syndrome which presents with wide manifestations leading to delayed diagnosis. A 34-year-old woman presented to our hospital complaining of dyspnea and productive cough. Lung CT scan revealed loculated right-sided pleural effusion with bronchiectasis and consolidation in right lower lobes. After taking medical history and physical examination, we suspected CVID and ordered serum immunoglobulin levels. The laboratory results were in line with CVID diagnosis and showed decreased levels of IgG, IgM, and IgA. The patient was started on intravenous immune globulin (IVIG) therapy every month. After 3-month follow-up, the patient reported no problem and felt better.